Revealing Purchase Intention as a Mediator Between Influencers and Gen Z Purchase Decisions - Martini, Ida Ayu Oka; Wijayanti, Ni Kadek Wiwin Asrya; Antara, Made Ermawan Yoga (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study will focus on the consumer behavior of generation Z in purchasing makeup products, namely by exploring makeup brand preferences among generation Z. For the wider community, this study can increase understanding of how purchasing decisions are influenced by social and digital factors, as well as the importance of digital literacy in dealing with the rapid flow of information. Methodology: This study aims to examine the influence of influencers on interest and purchasing decisions for Maybelline makeup products on Generation Z in Denpasar City, using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach. Generation Z was chosen because it is a digital-native generation with a high dependence on social media and the dominant population in Indonesia. The research sample consisted of 130 respondents selected using the purposive sampling method. Results: The results of the study show that influencers have a positive and significant effect on purchase intention, which means that choosing the right influencer can increase consumer interest. Purchase intention also has a positive and significant effect on purchase decisions, indicating that the higher the consumer interest, the more likely they are to buy the product. In addition, influencers also have a positive and significant direct effect on purchase decisions, confirming their important role in shaping consumer behavior. Findings: This study found that purchase intention mediates the relationship between influencers and purchase decisions. This means that purchase intention plays an important role in strengthening the influence of influencers on consumer decisions. Novelty: the results of this study strengthen the literature on the relationship between influencers, purchase intention, and purchase decisions in the digital era.Originality: This study provides practical implications for companies in selecting relevant influencers and designing appropriate marketing content for Generation Z. Conclusion: This study highlight the importance of influencer-based marketing strategies in increasing product appeal and conversion among Generation Z. Type of Paper: Research article.